Pharmacokinetic study of diclazuril in broiler after oral administration of single therapeutic dose (Journal of Hama University, 2022)
This study was carried out in order to determine the pharmacokinetic parameters of Diclazuril 2.5% preparation in broiler, where 20 broiler (Ross breed) with age of 45 days were used for this study. The broiler were randomly distributed into two groups, the first was considered a control group, consisting of ten birds given orally only distilled water, and the second group was the treatment group. Each bird in this group was given a dose of 1.25 mg/kg b. w, orally from Diclazuril 2.5% preparation once only, then blood samples were collected from the wing vein at different times: 6, 24, 48, 72, 120, 168, 240 hours after administration, in order to determine the time to reach the maximum concentration of diclazuril, and to determine the biological half-life ( T1/2) for the drug. The results showed that the time of peak concentration (Tmax) of diclazuril to reaches it’s the peak plasma concentration (Cmax) was six hours after administration, and the T1/2 of diclazuril 2.5% was 48±8 after administration approximately.